Changes of Essential Oil Content and Composition of Rose-Scented Geranium (Pelargonium Graveolens L’Her.) Cultivated at Different Province of Türkiye - Emine Bilginoğlu; Elif Ferahoğlu; Saliha Kırıcı (Turkish Journal of Agriculture: Food Science and Technology)
Pelargonium graveolens (rose-scented geranium) plants have been used since ancient times in food, cosmetics, perfumery, traditional medicine, and the pharmaceutical industries due to the pleasant fragrance of the essential oil obtained from its leaves. In this study, the essential oil content and components of rose-scented geranium cultivated in two different regions, Kırşehir in Central Anatolia and Adana in the Eastern Mediterranean, were investigated. The essential oil content of the plants from Kırşehir was determined to be 0.70%, while that of the plants from Adana was 0.34%. The main components of the essential oil of geranium cultivated in Kırşehir were citronellol (35.05%), geraniol (8.29%), and citronellyl formate (10.59%). In Adana, the essential oil components were citronellol (29.71%), geraniol (4.31%), and citronellyl formate (16.10%). The study shows that different locations significantly affect the essential oil content and chemical composition of rose-scented geranium.